2017
DOI: 10.1111/jocs.13085
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after mechanical aortic valve replacement with aortic root enlargement in adolescents

Abstract: BACKGROUND: Deciding which prosthetic aortic valve to choose is difficult in adolescents who

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…Both mAVR and bAVR have risks and benefits with bleeding events generally occurring more frequently with mAVR and SVD more prevalent for bAVR . However, the finding of increased bleeding events for mAVR is not consistent with recent studies …”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Both mAVR and bAVR have risks and benefits with bleeding events generally occurring more frequently with mAVR and SVD more prevalent for bAVR . However, the finding of increased bleeding events for mAVR is not consistent with recent studies …”
Section: Discussioncontrasting
confidence: 56%
“…Both patient‐ and prosthesis‐related factors should be taken into account prior to the recommendation of a valve choice by the surgeon. mAVR in the aortic position remain an excellent treatment option in adolescents and young adults with freedom from valve‐related events as high as 88% at 4 years . Both mAVR and bAVR have risks and benefits with bleeding events generally occurring more frequently with mAVR and SVD more prevalent for bAVR .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the introduction of the On‐X mAVR, INR levels as low as 1.8 have been shown to be safe and effective, thus further reducing the risk of bleeding complications . A mAVR has been a reliable prosthesis for adolescents and young adults, with freedom from valve‐related events as low as 88% at 4 years of follow‐up . Recent studies in adults have also shown no difference in bleeding complications between mAVR and bAVR …”
mentioning
confidence: 99%